A hypothesis of 'How Advertising Works' and implications for marketers and advertisers - Brian McMillan (Communicare)
THIS article discusses how consumers probably arrive at purchase decisions. It explains the purchase dynamics which Influ- ence the purchase of one product versus another product and one brand versus another brand within a given product cate- gory. From understanding how consumers arrive at buying decisions, a model is de- vised to suggest how those consumers can be approached with advertising and discus- ses why advertising content and style should be so different for different product categories. COMMUNICARE also encourage contri- butions from the industry to ensure a two- way flow of communication between theory and practice. Especially when these contri- butions show how theories and models studied in the communication discipline can be applied in practice, and in its turn stimulate further research.